An efficient Regeneration Protocol for in vitro Direct Organogenesis in Einkorn (Triticum monococcum L.) Wheat - Günce Şahin; Mehmet Örgeç; Nusret Zencirci (Journal of Agricultural Sciences)
Coleoptile, leaf, and root explants of the einkorn (Triticum monococcum ssp. monococcum) were cultured in vitro to obtain an efficient plant regeneration protocol through direct shoot formation by using different combinations and concentrations of various plant growth regulators. A total of 180 different auxin and cytokinin combinations were tested for regeneration. Shoot formation was not observed with the root and leaf explants. Shoot formation was obtained only from the coleoptile explants, with a mean of 1.20±0.24 shoots/explant and 86.60% of shoot formation frequency and with a 1.20±0.53 shoots/explant and 80.00% shoot formation frequency on medium supplemented with 0.5 mg L-1 TDZ and 1 mg L-1 TDZ plus 1 mg L-1 NAA, respectively. The shoots were subcultured on the MS medium containing the most effective hormonal combination concurrently continued to shoot and root formation for 45 days. It is noteworthy that 3.66±0.66 shoots per explant were induced by MS, which contained 1 mg L-1 TDZ plus 1 mg L-1 NAA and 2.0 mg L-1 KIN plus 0.5 mg L-1 NAA for 45 days. Of the different auxin concentrations tested for rooting, 2.0 mg L-1 IAA was predominant, with the greatest number of roots (12.33±0.88) produced per regenerated shoot. Finally, these well-developed plantlets were acclimatized with a 100% success rate and were transferred to the ex vitro conditions. A highly efficient regeneration protocol for einkorn wheat was developed using somatic tissue as an explant source for the first time.